Nonosmotic secretion of arginine vasopressin and salt loss in hyponatremia in Kawasaki disease. Issue 3 (28th January 2020) - Miura, Kenichiro; Harita, Yutaka; Takahashi, Naoto; Tsurumi, Haruko; Yasudo, Hiroki; Isojima, Tsuyoshi; Hirata, Yoichiro; Inuzuka, Ryo; Takizawa, Keiichi; Toyofuku, Etsushi; Nishimoto, Hajime; Takamizawa, Masaru; et al.
Abstract: Background: The precise mechanism of hyponatremia in Kawasaki disease (KD) remains elusive because assessment of volume status based on serial changes in body weight is lacking in previous reports. Methods: Seventeen patients who were diagnosed with KD and hyponatremia (serum sodium levels <135 mmol/L) were analyzed. Volume status was assessed based on serial changes in body weight. Plasma arginine vasopressin (ADH), urine electrolytes, and serum cytokine levels were measured on diagnosis of hyponatremia. An increase in body weight by >3% was defined as hypervolemia and a decrease in body weight by >3% was defined as hypovolemia. Results: The volume status was hypervolemic in three patients (18%), euvolemic in 14 (82%), and hypovolemic in none (0%). Five (29%) patients were diagnosed with "syndrome of inappropriate secretion of antidiuretic hormone" (SIADH) and no patients were diagnosed with hypotonic dehydration. The contribution of decreased total exchangeable cations (salt loss) to hyponatremia (5.9% [interquartile range, 4.3%, 6.7%]) was significantly larger than that of increased total body water (−0.7% [−1.8%, 3.1%]) ( P  = 0.004). Serum interleukin‐6 levels were elevated in all of the nine patients who were evaluated. Among the 12 (71%) patients who did not meet the criteria of SIADH and hypotonic dehydration, plasma ADH levels were inappropriately high in ten patients. These patients were also characterized by euvolemic or hypervolemic hyponatremia and salt loss, which might be compatible with a diagnosis of SIADH. Conclusions: Our study shows that hyponatremia in KD is euvolemic or hypervolemic and is associated with nonosmotic secretion of ADH and salt loss in the majority of patients.